PROGRAM PENA (PSIKOLOGI EDUKASI NIAT ANTISIPASI): SOSIALISASI UPAYA MITIGASI DAMPAK PERNIKAHAN DINI DI KELURAHAN SUKAGALIH GARUT - Nurhanah, Wanifa; Azmi Taqiyuddin, Muhammad; Ilham Pradana, Rafiali; Mauludin, Syahrul; Dita, Hanin; Alfathihah, Relianto; Ica Rahmanawati, Neng; Hermansyah, Risman; Moch Rizqi Nur Ihsan, Rafly; Anggraeni, Sifa; Perwito, Perwito (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2024)
The Community Service Program (KKN) of Muhammadiyah University of Bandung provides an opportunity for students to apply their knowledge in real-world contexts within the community. The service conducted by Regular Group 62 through the PENA Program (Psychological Education of Anticipatory Intent) aims to enhance public understanding of the impacts of early marriage and parental readiness. The methods used include observation, interviews, planning, implementation, and evaluation of activities. The results of the program demonstrate a high level of enthusiasm among participants, evident from their active involvement in question-and-answer sessions. This positive response reflects the community's commitment to learning and applying new knowledge. The material presented has been integrated into daily life, emphasizing the importance of education in raising awareness about child development and education. This program successfully created a positive wave, encouraging participants to be more proactive in addressing the challenges of early marriage.